PENGARUH CAR, NPL, DAN ROA TERHADAP PENYALURAN KREDIT USAHA RAKYAT (Studi Kasus pada PT Bank Rakyat Indonesia Tbk) - Prihartini, Suci; Dana, I Made (E-Jurnal Manajemen; Vol 7 No 3 (2018), 2018)
ABSTRACT   Bank Rakyat Indonesia has made a positive contribution in the development of SMEs in Indonesia with the Kredit Usaha Rakyat (KUR) program. Internal factors affecting the distribution of KUR, that is Capital Adequacy Ratio (CAR), Non Performing Loan(NPL), and Return On Assets (ROA), so this study aims to determine the effect of CAR, NPL on distribution of KUR with ROA as mediation. This research used the quantitative approach and case study at Bank Rakyat Indonesia 2009-2016. Data collection methode is nonparticipant observation by accessing website www.bri.co.id and used path analysis techniques with sub-structure model. Sub-structure I indicate that CAR, NPL significant effect on ROA and sub-structure II indicate that CAR, NPL, ROA have significant effect on the distribution of KUR. Sobel test indicate there is an indirect effect between CAR and NPL on distribution of KUR with ROA as mediation.   Keyword: Capital Adequacy Ratio (CAR), Kredit Usaha Rakyat (KUR) , Non Performing Loan (NPL), Return On Assets (ROA)